Electrical Conductivity and Optical Properties of Ploly(3-thiophene boronic acid) Organic Semiconductor - Yakuphanoğlu, Fahrettin; Senkal, B. Filiz (Wiley, 2009)
Electrical conductivity and optical properties of the poly(3-thiophene boronic acid) have been investigated. The room temperature electrical conductivity and activation energy of the poly(3-thiophene boronic acid) were 2.0 x 10(-9) S/cm and 0.17 eV, respectively. In the semiconductor region of the polymer, the charge transport mechanism is taking place by the hopping process in the localized states. The direct optical band gap value of the poly(3-thiophene boronic acid) was found to be 1.92 eV via optical absorption method. The width of localized states for the polymer was determined to be 0.36 eV. The refractive index dispersion curve of the polymer obeys the single oscillator model. The refractive index dispersion parameter E-o/S-o for the poly(3-thiophene boronic acid) was determined to be 9.82 x 10(12) eV m(2). The optical dielectric constants of the polymer were determined. The real part of the dielectric constant of the polymer is higher than that of imaginary part of the dielectric constant. The imaginary part shows a peak corresponding to the absorption edge. It is evaluated that the electrical and optical results of the poly(3-thiophene boronic acid) indicate that it is an organic semiconductor with electrical and optical parameters. POLYM. ENG. SCI., 49:722-726, 2009. (c) 2009 Society of Plastics Engineers
8th International Symposium on Polymer Physics -- JUN 01-05, 2006 -- Natl Res Council Canada, Boucherville, CANADA
Keywords: Plasma-Polymerized Thiophene; Band-Gap; Thin-Film; Stability